Phosphate fertilization associated with liming for the production of seedlings of Astronium fraxinifolium Schott. in red-yellow latosol (Research, Society and Development, 2022)
In acidic soils with low fertility, liming has the potential to increase the availability of phosphorus for plants, which may result in a lower demand for phosphate fertilizers. This study was carried out with the objective of evaluating the effects of liming and phosphate fertilization on the production of gonçalo-alves (Astronium fraxinifolium Schott.) seedlings. Seedlings at 10 days of age were transferred to plastic bags containing 6.0 kg of psamitic dystrophic Red-Yellow Latosol, collected in the layer 40 to 70 cm. The experiment was carried out in a greenhouse covered with a screen to retain 50% of the light. A randomized block design was adopted, in a 2x5 factorial scheme, with ten treatments, phosphate fertilization with five doses of phosphorus associated with the presence or absence of liming, with four replications, and with three seedlings per plot. Liming was performed with dolomitic limestone in sufficient quantity to raise the base saturation to 50%, associated or not with phosphate fertilization at doses of 0, 30, 60, 90 and 120 mg P kg-1. The seedlings were evaluated for height, diameter at 1.0 cm from the stem, leaf area, number of leaves and dry matter of shoots and roots. The growth of A. fraxinifolium was limited by the omission of phosphorus and lime in the soil. The phosphorus dose of 65 mg kg-1 should be adopted, as it is equivalent to 90% of the estimated dose for maximum growth in height and diameter of seedlings.